Can executive functions help to understand children with mathematical learning disorders and to improve instruction? - Desoete, Annemie; De Weerdt, Frauke (Learning disabilities (Weston, Mass.), 2013)
Working memory, inhibition and naming speed was assessed in 22 children with mathematical learning disorders (MD), 17 children with a reading learning disorder (RD), and 45 children without any learning problems between 8 and 12 years old. All subjects with learning disorders performed poorly on working memory tasks, providing evidence that they have a deficiency related to simultaneously storage and processing of verbal and/or visuospatial information. In addition, children with MD+RD suffered from problems with quantity naming speed compared to children without MD. Our data revealed the importance to manage working memory loads and give more time to complete homework, exercises, and examinations. Keywords: Executive functions, working memory, mathematical learning disorders, and math instruction.